Kinetics studies and mechanism evolution of the epoxidation of styrene over nanoporous Au doped TS-1 - Saxena, Samidha; Dwivedi, Reena; Bhadauria, Sheenu; Chumbhale, Vilas R.; Prasad, Rajendra (Polish Journal of Chemical Technology, 2010)
{A kinetic investigation of the slurry phase epoxidation of styrene with hydrogen peroxide has been carried out, for the first time, over nanoporous Au doped TS-1 catalyst, in a batch reactor, in the temperature range of 313-333 K. It was found that product selectivity and the rate of reaction are greatly influenced by concentrations of styrene and hydrogen peroxide. Kinetics studies reveal that the mechanism of the reaction is of the ``Redox'' type. The rate equation
Keywords: Au/TS-1; epoxidation; kinetics; styrene; Styrene oxide